ZnO@CDs composite catalytic material and preparation method and application thereof
Patent Information
- Application Number
- CN202611204298.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-09
AI Technical Summary
然而,该方法中量子点与ZnO之间主要通过物理吸附结合,界面结合力弱,在长期使用或超声振动条件下容易发生量子点脱落,导致催化活性衰减
(1)实现了CDs在ZnO表面的共价键锚定,界面结合力显著增强。本发明采用溶剂热原位生长策略,利用柠檬酸和尿素在高温DMF体系中的碳化缩合反应,使CDs在ZnO表面通过Zn-O-C共价键化学锚定,与现有物理混合法相比,界面结合强度更高,长期稳定性更好。
Smart Images

Figure CN122875207A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of environmental functional materials and advanced oxidation water treatment technology, and in particular to a ZnO@CDs composite catalytic material, its preparation method and application. Background Technology
[0002] With the rapid development of the industrial dyeing and printing industry, the discharge of organic dye wastewater is increasing day by day. This type of wastewater is characterized by high color, high toxicity, and poor biodegradability, posing a serious threat to aquatic ecosystems and human health. Traditional water treatment methods such as adsorption, coagulation sedimentation, and biological treatment are difficult to achieve complete mineralization of recalcitrant organic dyes. Therefore, the development of efficient and green advanced oxidation water treatment technologies is of great practical significance.
[0003] Photocatalysis, a typical advanced oxidation technology, utilizes reactive oxygen species (ROS) generated by semiconductor materials under light to oxidize and degrade organic pollutants. It offers advantages such as mild reaction conditions and no secondary pollution. Zinc oxide (ZnO), a common wide-bandgap semiconductor photocatalyst, boasts advantages such as low cost, non-toxicity, and high electron mobility. However, its wide bandgap (approximately 3.2 eV) limits its responsiveness to ultraviolet light (accounting for only about 4% of the solar spectrum), resulting in extremely low visible light utilization. Furthermore, its high recombination rate of photogenerated electron-hole pairs leads to unsatisfactory catalytic efficiency.
[0004] Piezoelectric catalysis is an emerging catalytic technology that utilizes the piezoelectric polarization field generated by non-centrosymmetric crystal materials under mechanical stress to drive carrier separation, thereby producing reactive oxygen species for pollutant degradation. ZnO, with its non-centrosymmetric hexagonal wurtzite structure, exhibits piezoelectric effects and can be used for piezoelectric catalysis. However, single piezoelectric or photocatalytic modes often suffer from limited catalytic efficiency and low energy utilization.
[0005] In existing technologies, researchers have attempted to composite carbon-based quantum dots with ZnO to improve the catalytic performance of ZnO-based materials. For example, the invention patent with application number CN202111038372.X discloses a graphene quantum dot-modified zinc oxide (GQDs / ZnO) catalyst prepared by physically mixing graphene quantum dots and ZnO at a mass ratio of 0.005~0.05:1 using a combination of solid-phase chemical method and stirring method. However, in this method, the quantum dots and ZnO are mainly bound by physical adsorption, resulting in weak interfacial bonding. Under long-term use or ultrasonic vibration conditions, quantum dots are prone to detachment, leading to a decrease in catalytic activity. Furthermore, in this technical solution, photocatalysis and piezoelectric catalysis are tested separately, without establishing a synergistic catalytic system in which the two act simultaneously, thus failing to utilize the synergistic effect of piezoelectric-photocatalysis.
[0006] In addition, the invention patent with application number CN201810036307.5 discloses a visible light catalyst with a zinc oxide@carbon nitride quantum dot (ZnO@C3N4QDs) composite structure, but its quantum dot type is carbon nitride quantum dots rather than carbon quantum dots, and it only involves visible light catalysis, not piezoelectric catalysis or piezoelectric-photocatalytic synergy.
[0007] In addition, the existing technology has the following technical defects: (1) It is not adaptable to weak light conditions and relies on high-energy light sources; (2) The contribution levels of various reactive oxygen species in the piezoelectric-photocatalytic synergistic system lack systematic quantitative analysis, which cannot provide clear mechanistic guidance for catalyst design and optimization.
[0008] Therefore, there is an urgent need for a composite catalytic material of zinc oxide modified with carbon quantum dots, its preparation method, and its application in the weak light-ultrasound synergistic catalytic degradation of organic dye wastewater, in order to solve the above problems. Summary of the Invention
[0009] The purpose of this invention is to provide a ZnO@CDs composite catalytic material, its preparation method, and its application. The material has strong interfacial bonding and good stability, and can achieve efficient catalytic degradation under weak light conditions. The synergistic catalytic efficiency is about 2.3 times that of light alone and 5.5 times that of ultrasound alone, making it suitable for the treatment of organic dye wastewater.
[0010] To achieve the above objectives, the present invention provides a method for preparing ZnO@CDs composite catalytic materials, comprising the following steps: S1. In proportion, zinc acetate dihydrate (Zn(CH3COO)2·2H2O) and hexamethylenetetramine (HMTA, C6H) 12 Using N4) as raw material, ZnO nanorod carriers were obtained by hydrothermal reaction at 80~100℃ for 4~16h. S2. According to the proportion, the ZnO nanorod support obtained in S1, citric acid as a carbon source, and urea as a nitrogen source are dispersed in N,N-dimethylformamide (DMF) and subjected to a solvothermal reaction at 180~220℃ for 4~12h to allow carbon quantum dots (CDs) to grow in situ on the surface of ZnO nanorods and be chemically anchored by Zn-OC covalent bonds. After washing and drying, ZnO@CDs composite catalytic material is obtained.
[0011] Preferably, in S1, the molar ratio of zinc acetate dihydrate to hexamethylenetetramine is 1:0.5~2, and more preferably 1:1 equimolar ratio.
[0012] Preferably, in S1, the hydrothermal reaction temperature is 89~91℃ and the reaction time is 8h. The resulting ZnO nanorods have a hexagonal wurtzite structure (JCPDS No. 36-1451), a length of 1~10μm, a diameter of 200~300nm, and a non-centrosymmetric crystal structure, thus exhibiting piezoelectric effect.
[0013] Preferably, in S2, the mass ratio of citric acid to urea is 1~5:1, more preferably 2.3~2.4:1.
[0014] Preferably, in S2, the solvothermal reaction temperature is 200℃ and the reaction time is 8h. The resulting carbon quantum dots have a size ≤10nm, are rich in hydroxyl, carboxyl, and amino functional groups, and are attached to the surface of ZnO nanorods in an approximately spherical particle morphology.
[0015] This invention also provides a ZnO@CDs composite catalytic material, comprising a ZnO nanorod support and carbon quantum dots anchored to the surface of the ZnO nanorod support. A direct Z-shaped heterojunction is formed between the ZnO nanorod support and the carbon quantum dots. The ZnO nanorod support has a hexagonal wurtzite structure with a hexagonal prism-shaped morphology, a length of 5-25 μm, and a diameter of 200-300 nm. The carbon quantum dots have a size ≤10 nm and are chemically anchored to the surface of the ZnO nanorod support via Zn-OC covalent bonds. Under the simultaneous action of weak light and ultrasound, the ZnO@CDs composite catalytic material generates superoxide radicals (·O2). - A reactive oxygen species system with hydroxyl radicals (·OH) as the primary dominant group and hydroxyl radicals (·OH) as the secondary dominant group.
[0016] This invention also provides an application of ZnO@CDs composite catalytic material in the catalytic degradation of organic dyes, wherein the method for catalytic degradation of organic dyes specifically comprises: The ZnO@CDs composite catalytic material was dispersed in the water containing organic dyes to be treated. After reaching adsorption-desorption equilibrium by stirring in the dark, the reaction system was simultaneously subjected to weak light and ultrasonic vibration. Under the synergistic effect of piezoelectric and photocatalysis, the organic dyes were oxidatively degraded.
[0017] Preferably, the illuminance range of the weak light is 10,000 to 50,000 Lux, and the power range of the ultrasonic vibration is 50 to 200 W, and the frequency range is 20 to 100 kHz.
[0018] Preferably, the illuminance of the weak light is 27000 Lux, and the power of the ultrasonic vibration is 100W and the frequency is 40kHz.
[0019] Preferably, the organic dye is a cationic dye, including one or more of methylene blue, methyl violet, or rhodamine B.
[0020] Preferably, the amount of the ZnO@CDs composite catalyst is 10-50 mg / 20 mL of dye solution, and the initial concentration of the organic dye is 5-50 mg·L⁻¹. -1 .
[0021] The synergistic catalytic mechanism of this invention is as follows: Under weak light excitation, both ZnO and CDs generate photogenerated electron-hole pairs; simultaneously, ultrasonic vibration causes periodic deformation of the non-centrosymmetric wurtzite ZnO lattice, generating a built-in electric field within the crystal through the piezoelectric effect. This built-in electric field tilts the energy bands, driving photogenerated electrons to transfer along a Z-shaped path from the ZnO conduction band to CDs, while holes remain in the ZnO valence band, thereby achieving efficient spatial separation of electron-hole pairs and effectively suppressing carrier recombination. The separated electrons react with dissolved O2 to generate superoxide radicals (·O2). - (the first dominant active species), holes and H2O / OH - The reaction generates hydroxyl radicals (·OH, the second dominant reactive species), which oxidize and degrade organic dye molecules step by step, eventually mineralizing them into CO2, H2O and inorganic ions.
[0022] Therefore, the present invention employs the above-mentioned ZnO@CDs composite catalytic material, its preparation method, and its application, and the beneficial effects are as follows: (1) Covalent anchoring of CDs on the ZnO surface was achieved, and the interfacial bonding strength was significantly enhanced. The present invention adopts a solvothermal in-situ growth strategy, utilizing the carbonization condensation reaction of citric acid and urea in a high-temperature DMF system to chemically anchor CDs on the ZnO surface through Zn-OC covalent bonds. Compared with the existing physical mixing method, the interfacial bonding strength is higher and the long-term stability is better.
[0023] (2) A weak light-ultrasound synergistic catalytic system was established, with catalytic efficiency far exceeding that of simple superposition of single modes. In this invention, methylene blue was used as a model dye. The apparent rate constant under synergistic conditions was significantly greater than the sum of the rate constants of light irradiation and ultrasound irradiation alone, satisfying the synergistic effect criterion. The synergistic catalytic efficiency was approximately 2.3 times that of light irradiation alone and 5.5 times that of ultrasound irradiation alone.
[0024] (3) The light response range is broadened, enabling efficient catalysis under low light conditions. This invention modifies CDs synthesized from citric acid / urea, utilizing the intermediate energy levels and photosensitization effects generated by the oxygen- and nitrogen-containing functional groups on the surface of CDs to effectively broaden the light response range of ZnO into the visible light region. This allows the catalyst to achieve a 90% degradation rate of methylene blue under simulated low light conditions of approximately 27,000 Lux, reducing dependence on traditional strong light sources.
[0025] (4) This invention provides the first systematic and quantitative analysis of the ROS contribution hierarchy in a piezoelectric-photocatalytic synergistic system. Through systematic capture experiments of four active species, this invention determined the contribution hierarchy of each ROS to be ·O2. - (First Dominant) •OH (second dominant) > H2O2 (moderate contribution) 1 O2 (negligible) provides a theoretical basis for the selective regulation of catalysts.
[0026] (5) The preparation process is simple, the raw materials are inexpensive, and the applicability is wide. The preparation method of this invention only requires two steps: hydrothermal and solvothermal reaction. The equipment requirements are low, the operation is simple, and it is easy to scale up. The raw materials are all conventional industrial reagents, which are inexpensive and readily available. The synthesis process does not use precious metals or highly toxic reagents, making it green and environmentally friendly.
[0027] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0028] Figure 1 The image is a scanning electron microscope (SEM) image of ZnO NRs prepared in Example 1 of the present invention at a magnification of 5kX. Figure 2 The images show the morphology of ZnO@CDs prepared in Example 1 of this invention, where (a) is a SEM image and (b) is a transmission electron microscope (TEM) image. Figure 3 The X-ray diffraction (XRD) patterns of ZnO NRs and ZnO@CDs prepared in Example 1 of this invention; Figure 4 This is a comparison of the degradation curves of ZnO@CDs on methylene blue (MB) under three conditions: light irradiation + ultrasound (synergistic), light irradiation alone, and ultrasound alone, in Example 2 of the present invention. Figure 5 This is a comparison of the degradation curves of MB by ZnO@CDs and pure ZnO nanorods under the combined conditions of light irradiation and ultrasound in Example 2 of the present invention. Figure 6 This is a comparative bar chart showing the apparent rate constant k of MB degradation reaction under three conditions in Example 2 of the present invention; Figure 7 This is a summary diagram of the degradation of different dyes (MB, MV, RhB, MO) by ZnO@CDs under the combined conditions of light and ultrasound in Example 3 of the present invention. Figure 8The figures shown are experimental results of the ZnO@CDs system capturing reactive oxygen species in the embodiments of the present invention. Among them, (a) is the absorbance change curve of singlet oxygen, (b) is the absorbance change curve of captured hydrogen peroxide, (c) is the absorbance change curve of captured superoxide radical, and (d) is the absorbance change curve of captured hydroxyl radical. Figure 9 This is a schematic diagram of the mechanism of Z-type heterojunction photo-piezoelectric synergistic catalytic degradation of organic dyes in the ZnO@CDs composite catalytic material in this embodiment of the invention; Figure 10 This is a SEM image of the ZnO@CDs composite catalyst material after three cycles in an embodiment of the present invention. Detailed Implementation
[0029] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments.
[0030] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains. Unless otherwise specified, the experimental methods in all embodiments of this invention are conventional methods; all reagents used, unless otherwise specified, are commercially available, are of analytical grade, and are used directly without further purification; the experimental water is ultrapure deionized water (resistivity >18.2 MΩ·cm, 25°C).
[0031] Example 1 A ZnO@CDs composite catalytic material is prepared by the following method: (1) Preparation of ZnO nanorod supports: Weigh 548.6 mg (2.5 mmol) of Zn(CH3COO)2·2H2O and dissolve it in 125 mL of ultrapure deionized water. Sonicate the solution to obtain a colorless and transparent solution A. Weigh 350.4 mg (2.5 mmol) of hexamethylenetetramine and dissolve it in 125 mL of ultrapure deionized water. Sonicate the solution to obtain a colorless and transparent solution B. Mix solutions A and B and stir magnetically for 30 min until homogeneous to obtain a ZnO nutrient solution (total volume approximately 250 mL, with a zinc acetate to HMTA molar ratio of 1:1).
[0032] 25 mL of the ZnO nutrient solution was transferred to a 50 mL PTFE-lined stainless steel high-pressure reactor, sealed, and placed in a forced-air drying oven for hydrothermal reaction at 90 ± 1 °C for 8 h. After natural cooling to room temperature, the white flocculent product in the reactor was vacuum filtered (using an organic filter membrane with a pore size of 0.22 μm), and washed three times each with deionized water and anhydrous ethanol (approximately 20 mL each time). The solid product collected on the filter membrane was placed in a vacuum drying oven and dried at 60 °C for 12 h. The product was then scraped off with a spatula and thoroughly ground to obtain white powdery ZnO nanorods (denoted as ZnO NRs).
[0033] (2) Preparation of ZnO@CDs composite catalytic material: Weigh out an appropriate amount of ZnO nanorod powder (350 mg) and measure 25 mL of DMF as solvent. Weigh out 350 mg of citric acid monohydrate (carbon source, C6H8O7·H2O, analytical grade) and 150 mg of urea (nitrogen source, CO(NH2)2, analytical grade), i.e., the mass ratio of citric acid to urea is approximately 2.3:1. Add the ZnO nanorod powder, citric acid monohydrate, and urea to the DMF, stir and disperse evenly, then transfer to a 50 mL polytetrafluoroethylene-lined stainless steel high-pressure reactor. Seal the reactor and place it in a forced-air drying oven for solvothermal reaction at 200 °C for 8 h.
[0034] After natural cooling to room temperature, the reaction solution was diluted with ultrapure water at a volume ratio of approximately 1:5, and the solid product was separated by vacuum filtration. The solid on the filter membrane was washed three times with anhydrous ethanol (approximately 20 mL each time) to remove free CDs not anchored to the ZnO surface. The collected solid product was dried in a vacuum drying oven at 60°C for 12 h, and then ground to obtain a grayish-brown powdered ZnO@CDs composite catalyst. The yield (based on the amount of ZnO input) in this example was approximately 32.80%.
[0035] The reason for the yield being less than 100% is mainly that some ZnO nanorods were broken and lost during the solvothermal and subsequent washing processes, and some CDs were not successfully anchored to the ZnO surface and were removed during the washing step.
[0036] like Figure 1 As shown, at a magnification of 5kX, ZnO NRs exhibit a typical hexagonal prism rod structure with a length of approximately 24±0.5μm and a diameter of 220±50nm. Figure 2 As shown in (a), after CDs modification, the main hexagonal rod-shaped morphology of ZnO was completely preserved, indicating that the 200℃ solvothermal process did not damage the rod-shaped structure of ZnO. Figure 2 As shown in (b), a large number of light-contrast, approximately dot-shaped nanoparticles are attached to the surface and edges of the ZnO nanorods. The size of these nanoparticles is less than 10 nm. These particles are carbon quantum dots (CDs) grown in situ.
[0037] like Figure 3As shown, the ZnO NRs curve in the XRD pattern shows that the positions and relative intensities of all diffraction peaks correspond one-to-one with the standard card (JCPDS No. 36-1451) of hexagonal wurtzite ZnO. Among them, the (002) peak has a higher relative intensity, indicating that ZnO has a preferred orientation growth characteristic along the c-axis. The ZnO@CDs curve in the XRD pattern shows that the positions and relative intensities of the diffraction peaks are basically consistent with those of pure ZnO NRs, and can all be attributed to hexagonal wurtzite ZnO, indicating that the solvothermal CDs modification process did not change the crystal structure of ZnO.
[0038] Example 2 An application of a ZnO@CDs composite catalytic material in weak light-ultrasound synergistic catalytic degradation: Based on the ZnO@CDs composite catalytic material prepared in Example 1, the catalytic degradation of methylene blue (MB) is carried out. The specific steps are as follows: (1) Weigh 20.0 mg of the ZnO@CDs composite catalyst material prepared in Example 1 and add 20.0 mL of methylene blue solution (initial concentration 10.0 mg·L⁻¹). -1 The mixture was prepared with ultrapure deionized water. The solution was placed in a constant temperature water bath at 25±1℃ and magnetically stirred for 30 minutes in the dark to reach adsorption-desorption equilibrium (this point is recorded as 0 min of degradation). Then, a simulated weak light source (illuminance 27000 Lux, corresponding to an irradiance of approximately 40 mW·cm²) was simultaneously turned on. -2 The synergistic catalytic degradation reaction was initiated in a constant temperature water bath (25±1℃) using an ultrasonic cleaner (100W power, 40kHz frequency) and an ultrasonic cleaner.
[0039] (2) Take 3.0 mL samples at 30, 60, 90 and 120 min of reaction, separate the catalyst by centrifugation at 10000 rpm for 5 min, take the supernatant and measure the absorbance of MB at 664 nm with a UV-Vis spectrophotometer, calculate the removal rate, and obtain the apparent rate constant k by fitting the pseudo-first-order kinetics.
[0040] Calculate the removal rate R according to equation (1), and calculate the apparent rate constant k according to equation (2): R=(1-A t / A0)×100% (1; ln(A0 / A t )=k·t (2; In the formula: A0 is the initial absorbance, A t The absorbance at degradation time t is given by k, where k is the apparent first-order reaction rate constant (min). -1 ).
[0041] (3) Comparison with pure ZnO NRs: Under the same synergistic conditions, a comparative experiment was conducted using pure ZnO NRs (20.0 mg) prepared in Example 1 to replace the ZnO@CDs composite catalyst.
[0042] (4) Comparison of different excitation modes: Under the same conditions of catalyst dosage, initial MB concentration, reaction temperature and total reaction time, three parallel experiments were set up: the ultrasonic group alone (only the ultrasonic cleaner was turned on, and no light was applied), the light group alone (only the simulated weak light source was turned on, and no ultrasound was applied), and the synergistic group (light + ultrasound).
[0043] like Figure 4 As shown, the MB degradation rate of the synergistic group reached about 90% at 120 min, which was much higher than that of the light-only group (about 62.9%) and the ultrasound-only group (about 44.5%).
[0044] like Figure 5 As shown, pure ZnO NRs degraded MB by 70% under synergistic conditions for 120 min, while ZnO@CDs degraded MB by 90%, an increase of about 20 percentage points. This indicates that the introduction of CDs effectively optimized the material system and significantly improved the catalytic performance.
[0045] like Figure 6 As shown, the comparison of the apparent rate constants under the three sets of conditions is as follows: k for the cooperative group US+UV =0.01317min -1 Individual illumination group k UV =0.00565min -1 ultrasound group alone k US =0.00238min -1 The apparent rate constant (k) when both light and ultrasound are applied simultaneously. US+UV The rate constant (k) is significantly greater than that under single illumination. UV ) and the rate constant (k) during ultrasound alone US The sum of ( ). When this inequality holds, it can be determined that there is a synergistic enhancement effect rather than a simple superposition.
[0046] After calculation, k US+UV (0.01317) > k US +k UV (0.00803) satisfies the synergistic effect criterion, proving that there is a significant synergistic enhancement effect between weak light illumination and ultrasonic vibration, rather than a simple superposition.
[0047] The synergistic catalytic mechanism is as follows: Under weak light excitation, both ZnO and CDs generate photogenerated electron-hole pairs. Simultaneously, ultrasonic vibration causes periodic deformation of the non-centrosymmetric wurtzite ZnO lattice, generating a built-in electric field within the crystal through the piezoelectric effect. This built-in electric field tilts the energy bands, driving photogenerated electrons to transfer along a Z-shaped path from the ZnO conduction band to CDs (the Fermi level of CDs synthesized from citric acid / urea is favorable for accepting electrons from ZnO, conforming to the thermodynamic conditions of the Z-shaped path), while holes remain in the ZnO valence band, thus achieving efficient spatial separation of electron-hole pairs and effectively suppressing carrier recombination. The separated electrons react with dissolved O2 to generate superoxide radicals (·O2). - (the first dominant active species), holes and H2O / OH - The reaction generates hydroxyl radicals (·OH, the second dominant reactive species), along with the formation of hydrogen peroxide (H₂O₂) as a reaction intermediate. These ROS progressively oxidize and degrade organic dye molecules, ultimately mineralizing them into CO₂, H₂O, and inorganic ions (such as NO₃⁻). - SO4 2- (etc.). Among them, ·O2 - The reason why the Z-shaped path makes the most significant contribution is that it enables electrons to be efficiently enriched at the CDs end, and the abundant oxygen-containing functional groups on the CDs surface are conducive to the adsorption of O2 and single-electron reduction.
[0048] Example 3 An application of a ZnO@CDs composite catalytic material in weak light-ultrasound synergistic catalytic degradation was described. Based on the ZnO@CDs composite catalytic material prepared in Example 1, the difference from Example 2 was that the catalytic degradation of methylene blue (MB) was replaced with methyl violet (MV), with an initial concentration of 10.0 mg·L⁻¹. -1 (Detection wavelength 583 nm), Rhodamine B (RhB, initial concentration 10.0 mg·L⁻¹) -1 The detection wavelength was 553 nm, and the initial concentration of methyl orange (MO) was 10.0 mg·L⁻¹. -1 (Detection wavelength 464nm).
[0049] like Figure 7 As shown, the degradation efficiencies of the four dyes are ranked as follows: MB > MV ≈ RhB > MO. The degradation efficiency of cationic dyes is significantly higher than that of anionic dyes. This is because the first dominant active species generated in the synergistic catalytic system is superoxide radical (·O2). - O2 itself carries a negative charge and has an electrostatic attraction with cationic dyes, accelerating the reaction of O2. - The degradation rate is slow due to the diffusion and attack of dye molecules. Electrostatic repulsion exists between MO and anionic dyes, and the azo bond (–N=N–) structure of MO is more stable.
[0050] Test 1. Experiments and mechanism verification of reactive oxygen species (ROS) capture, specifically: 10 mg of the ZnO@CDs composite catalyst prepared in Example 1 was weighed and subjected to photocatalysis and ultrasound synergistic treatment of MB (initial concentration 10.0 mg·L⁻¹). -1 Degradation experiments were conducted. Four capture experiments and one blank control were set up: (a) Singlet oxygen ( 1 O2) Capture: Add 1,3-diphenylisobenzofuran (DPBF) to a final concentration of 0.1 mmol / L for selective capture. 1 O2; (b) Hydrogen peroxide (H2O2) capture: 1 mg of potassium permanganate (KMnO4) was added to capture H2O2; (c) Superoxide radicals (·O2) - Capture: Add 1 mg of nitrotetrazole blue chloride (NBT) for capturing O2. - ; (d) Capture of hydroxyl radicals (·OH): 10 mg of terephthalic acid (TA) was added to capture ·OH; (e) Blank control: No capture agent was added, and an equal volume of ultrapure water was used instead.
[0051] Using the MB degradation rate constant k0 of the blank control group without any capture agent as a benchmark, the quenching efficiency of each capture experiment was calculated.
[0052] Calculate the quenching efficiency of each group of capture experiments according to formula (3): Quenching efficiency = (k0 - k q ) / k0×100% (3; In the formula: k0 is the rate constant of the blank control group, k q The rate constant after the addition of the trapping agent.
[0053] like Figure 8 As shown, NBT (·O2) is added. - After the superoxide radical (·O2) was scavenged, the MB degradation reaction almost completely stopped, and the quenching efficiency was close to 100%, proving that the superoxide radical (·O2) degradation reaction was effectively stopped. - ) is the most important and absolutely dominant active species in this synergistic catalytic system; the degradation was significantly inhibited after the addition of TA (·OH scavenger), proving that ·OH is the second dominant active species; the degradation efficiency decreased moderately after the addition of KMnO4 (H2O2 scavenger), indicating that H2O2 participates in the oxidation process as an important intermediate in the reaction network; the addition of DPBF ( 1 The degradation curve of the O2 scavenger largely overlapped with that of the blank control, indicating that... 1The amount of O2 generated is extremely small, and its contribution to the oxidative degradation of MB is negligible. In summary, the ROS contribution hierarchy in the ZnO@CDs piezoelectric-photocatalytic synergistic system is as follows: ·O2 - (First Dominant) •OH (second dominant) > H2O2 (moderate contribution) 1 O2 (negligible).
[0054] Based on the above experimental evidence, such as Figure 9 As shown, this invention proposes a Z-type heterojunction synergistic catalytic mechanism: Under weak light excitation, both ZnO and CDs generate photogenerated electron-hole pairs; simultaneously, ultrasonic vibration causes periodic deformation of the non-centrosymmetric wurtzite ZnO lattice, generating a built-in electric field within the crystal through the piezoelectric effect. This built-in electric field tilts the energy bands, driving photogenerated electrons to transfer along a Z-type path from the ZnO conduction band to CDs, where they recombine with holes in the CDs valence band. Meanwhile, high-energy electrons are retained in the CDs conduction band for O2 reduction to generate ·O2. - ZnO retains high-energy holes in its valence band for use in H2O / OH - Oxidation generates ·OH. This Z-type charge transfer mechanism achieves both efficient spatial separation of electron-hole pairs and sufficient redox capacity at both ends, which is key to achieving efficient synergistic catalysis.
[0055] The criteria for identifying Z-type heterojunctions: Unlike traditional type II heterojunctions (where electrons and holes transfer in opposite directions and accumulate on different sides, typically only one type of ROS can be efficiently generated), the ZnO@CDs system of this invention simultaneously generates a large amount of O2. - The presence of both ·OH and ·OH ROS indicates that ZnO and CDs each retain sufficient redox capabilities—a typical characteristic of Z-type heterojunctions (electrons transfer from the ZnO conduction band to the CDs valence band to recombine with holes; the CDs conduction band retains high-energy electrons for O2 reduction; and the ZnO valence band retains high-energy holes for H2O / OH). - (Oxidation).
[0056] 2. Catalyst recycling performance test: After completing one round of MB degradation reaction (120 min), the reaction solution was centrifuged at 10000 rpm for 5 min to recover the ZnO@CDs composite catalyst material. It was washed three times with deionized water, vacuum dried at 60℃, and then subjected to the next round of degradation experiment under the same conditions as in Example 2. Experimental results show that the catalyst can be recovered and reused through centrifugation. Figure 10 As shown, the SEM images after three cycles show that the ZnO@CDs microrods retain their morphology intact, with no obvious fractures, dissolutions or surface corrosion, confirming the excellent structural stability of the material imparted by the chemical anchoring strategy.
[0057] Therefore, the present invention adopts the above-mentioned ZnO@CDs composite catalytic material and its preparation method and application. The material has strong interfacial bonding and good stability, and can achieve efficient catalytic degradation under weak light conditions. The synergistic catalytic efficiency is about 2.3 times that of light alone and 5.5 times that of ultrasound alone, and it is suitable for the field of organic dye wastewater treatment.
[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a ZnO@CDs composite catalytic material, characterized in that, Includes the following steps: S1. Using zinc acetate dihydrate and hexamethylenetetramine as raw materials, ZnO nanorod carriers are obtained by hydrothermal reaction at 80-100℃ for 4-16 hours in a certain proportion. S2. According to the proportion, the ZnO nanorod support obtained in S1, citric acid as a carbon source and urea as a nitrogen source are dispersed in N,N-dimethylformamide and reacted solvothermically at 180~220℃ for 4~12h. After washing and drying, ZnO@CDs composite catalytic material is obtained.
2. The preparation method of a ZnO@CDs composite catalytic material according to claim 1, characterized in that, In S1, the molar ratio of zinc acetate dihydrate to hexamethylenetetramine is 1:0.5~2.
3. The preparation method of a ZnO@CDs composite catalytic material according to claim 1, characterized in that, In S1, the hydrothermal reaction temperature is 89~91℃ and the reaction time is 8h.
4. The preparation method of a ZnO@CDs composite catalytic material according to claim 1, characterized in that, In S2, the mass ratio of citric acid to urea is 1~5:
1.
5. The preparation method of a ZnO@CDs composite catalytic material according to claim 1, characterized in that, In S2, the solvothermal reaction temperature is 200℃ and the reaction time is 8h.
6. A ZnO@CDs composite catalytic material prepared by the method described in any one of claims 1 to 5, characterized in that: The ZnO@CDs composite catalytic material comprises a ZnO nanorod support and carbon quantum dots anchored on the surface of the ZnO nanorod support. A direct Z-shaped heterojunction is formed between the ZnO nanorod support and the carbon quantum dots. The ZnO nanorod support has a hexagonal wurtzite structure with a hexagonal prism rod shape, a length of 15~25μm, and a diameter of 200~300nm. The carbon quantum dots have a size ≤10nm and are chemically anchored to the surface of the ZnO nanorod support through Zn-OC covalent bonds.
7. The application of a ZnO@CDs composite catalytic material prepared by the method described in any one of claims 1 to 5, or the ZnO@CDs composite catalytic material as described in claim 6, in the catalytic degradation of organic dyes, characterized in that, The method for catalytic degradation of organic dyes specifically includes: The ZnO@CDs composite catalytic material was dispersed in the water containing organic dyes to be treated. After reaching adsorption-desorption equilibrium by stirring in the dark, the reaction system was simultaneously subjected to weak light and ultrasonic vibration. Under the synergistic effect of piezoelectric and photocatalysis, the organic dyes were oxidatively degraded.
8. The application according to claim 7, characterized in that, The illuminance range of the weak light is 10,000 to 50,000 Lux, and the power range of the ultrasonic vibration is 50 to 200 W, and the frequency range is 20 to 100 kHz.
9. In the application according to claim 7, the amount of the ZnO@CDs composite catalyst is 10-50 mg / 20 mL of dye solution, and the initial concentration of the organic dye is 5-50 mg·L⁻¹. -1 .
10. The application according to claim 7, characterized in that: The organic dye is a cationic dye, including one or more of methylene blue, methyl violet, or rhodamine B.
Citation Information
Patent Citations
A method for preparing a zinc oxide@carbon nitride quantum dot composite visible light photocatalyst
CN108212191B
A method for preparing graphene quantum dot-modified zinc oxide and its application in degrading dyes
CN113713798B